Temporal and spatial composition of arboreal insects along the Omaruru River, Namibia - Theron, Louise (University of the Free State, 2010)
Insects play a major role in any ecosystem and are also of extreme importance to the well-being of humans. Amongst others, they are pollinators that indirectly determine food security. On a more negative side, they can cause great crop damage and act as vectors for many diseases. It is thus of utmost importance to understand their biology. In this context a study was undertaken to analyze the temporal and spatial composition of arboreal insects along the Omaruru River in central Namibia. This river is one of the ephemeral rivers in Namibia, running along an east-west rainfall and altitudinal gradient. Three typical Namibian tree species (Acacia erioloba, Acacia tortilis and Faidherbia albida) were selected as host species and their canopies sampled over a period of one year. An anaesthetising insecticide, Pyrethroid, was used to fog the tree. Insects dropped onto plastic sheets suspended underneath each sample tree. This material was collected, stored in 70% Ethanol and then sorted and identified into relative taxonomic units (RTUs). The data obtained was used to compare the insect diversity and composition of the three selected host species. Results indicated that there are no statistical differences regarding canopy associated insects between the three tree species. Not only do they have similar numbers of RTUs, but they also share a high percentage (50% and higher) of the same RTUs. The influence of aridity was also investigated by comparing the different sampling stations with each other. The stations lie within different rainfall regimes and show an increase in mean temperature and a decrease in humidity from east to west. The effect of rainfall was eliminated because the trees make use of year-round groundwater to fulfil their requirements. Results indicated that the sampling stations differ from each other with regard to their insect diversity. The further apart the stations are from each other the less similar they are regarding recorded arboreal insect diversity. There was a noticeable decrease in RTU numbers from east to west. Lastly the effect of seasonality was also investigated. Samples were taken on a bi-monthly, basis allowing comparison of the three main seasons (pre-rainy, rainy and dry). Results indicated an increase during and after the rainy season and a decrease during the dry season. Finally, when deciphering the temporal and spatial composition of arboreal insects along the Omaruru River in Namibia, seasonality seem to be the most meaningful determining factor, followed by locality (site), in turn followed by host (tree) species. These results are largely in accordance with the results of other studies and, when linked to climate change, can provide valuable information to decision makers on various levels. An increase in temperature can cause a shift in insect distribution into areas presently not occupied by them, changing ecosystem function of the area (e.g. insect-plant interaction and disease transmission) in the process.

Insekte speel ‘n betekenisvolle rol in enige ekosisteem en is as sulks ook belangrik vir die vooruitgang van die mens. Onder andere is hulle bestuiwers wat indirek voedselsekuriteit bepaal. Aan die negatiewe kant veroorsaak hulle ook aansienlike oesskade en is hulle draers van baie siektes. Dit is dus van uiterste belang dat hulle biologie, diversiteit en volopheid ontleed en verstaan word. In hierdie konteks is ‘n studie van die verspreiding en samestelling van insekte oor tyd en ruimte langs die Omaruru Rivier in sentraal Namibië uitgevoer. Hierdie rivier is een van die nie-standhoudende riviere in Namibië en volg ’n oos-wes reënval- en hoogte bo seevlak gradient. Drie boomsoorte tipies aan Namibië (Acacia erioloba, Acacia tortilis en Faidheria albida) is gekies as gasheer spesies en opnames in die loof van die bome is oor ’n periode van een jaar gedoen. ’n Verdowende insekdoder, Pyrethroid, is gebruik om die bome te berook wat gelei het tot die afval van insekte op plastiek seile wat onder elke boom gespan is. Hierdie materiaal is versamel en in 70% Etanol gestoor, waarna hulle gesorteer en geïdentifiseer is as relatiewe taksonomiese eenhede (RTU’s) vir elke orde. Die versamelde data is gebruik om die insek diversiteit en samestelling van die drie gasheer spesies te vergelyk. Resultate het aangetoon dat daar geen statistiese verskille, wat betref loof-geassosieerde insekte, tussen die drie boom spesies bestaan nie. Nie alleen het hulle min of meer dieselfde getal taksonomiese eenhede nie, maar hulle deel ook ’n groot persentasie (50% en meer) van dieselfde taksonomiese eenhede. Die invloed van ariditeit is ook ondersoek deur die verskillende opname stasies met mekaar te vergelyk. Die stasies val in verskillende reënval streke en toon ‘n toename in temperatuur en afname in humiditeit van oos na wes. Die uitwerking van reënval is nie in berekening gebring nie omdat die bome van ondergrondse water, wat dwarsdeur die jaar beskikbaar is gebruik maak om aan hulle behoeftes te voldoen. Resultate het aangetoon dat die opnamestasies wel van mekaar verskil ten opsigte van hul insekdiversiteit. Hoe verder die stasies van mekaar geleë is, hoe meer verskil hulle van mekaar wat betref versamelde loof insekdiversiteit. Daar was ’n merkbare afname in taksonomiese eenhede van oos na wes. Die effek van seisoenaliteit is ook ondersoek. Opnames is op ’n twee-maandelikse basis gedoen wat dus daartoe gelei het dat al drie die seisoene (voor-reën, reën en droë) met mekaar vergelyk kon word. Resultate het ’n toename in getalle aangetoon gedurende en na die reënseisoen en ’n afname gedurende die droë seisoen. Ten slotte, wanneer die samestelling van insekte oor tyd en ruimte langs die Omaruru Rivier in Namibië ontleed word, blyk dit dat seisoenaliteit die mees bepalende faktor is, gevolg deur lokaliteit (versamelplek), om die beurt gevolg deur gasheer (boom) spesie. Hierdie resultate is grootliks in ooreenstemming met ander studies en wanneer dit gekoppel word aan klimaatsveranderinge kan dit van groot waarde vir besluitnemers op verskeie vlakke wees. ‘n Toename in temperatuur kan aanleiding gee tot ‘n verskuiwing in insek verspreiding na gebiede waar hul voorheen nie voorgekom het nie, wat sodoende edosisteem funksie (bv. Insek-plant interaksie en siekteoordrag) in die gebied kan verander.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2010
Keywords: Insect diversity; Host species; Aridity; Seasonality; Relative taxonomic units; Climate change; Insect surveys -- Namibia -- Omaruru River; Insect populations -- Namibia -- Omaruru River; Insect-plant relationships -- Namibia -- Omaruru River; Trees -- Namibia -- Omaruru River; Omaruru River (Namibia)